Organização de uma bateria de testes para seleção de candidatos ao ensino técnico de 2. grau - Ibarra de Candia, Maria Victoria (1984)
The program presented here relates an exploratory study in the area Technical - Industrial Education, at the secondary level, which objetive consisted in selecting among various tests the best in the Academic level for the Professional Formation, in order to form part of the group of tests that will be utilized in the candidates selection for the courses offered by the National Technical School for the informations of technicians in the intermediate level. This study was ma de through the cooperation of the 'Technical Education' and 'Educational and Vocational Guidance' Departaments, both of the M inistry of Education of Paraguay. It is part of the expansion project of counseling, at level of the Industrial - Techinician and Professional Formation, which one of the objetives is to control the quality of the enrrollment in order to avoid desertions and support the charge of the course offered at this level, 'which will be through the implementation, LY). all schools using this type of program, to evaluate the aptitudes and interest for improvement of the Human Recourses in developed countries. A careful analisis of the programs that will make up the curriculum in each speciality with the purpose to accomplish a list of aptitudes and characteristic give the professional specifications of each programe. Was esperimentated thirteen (13) Psichometric tests, one of ocupational interest and two of personality. It were thereafter treated with statistical methods in order to know its reliability and validity (criterio relation), the Academical application in the professional matter, the follwing tests were selected: Inteligencia Nao Verbal, Space reasoning Ribakow and Speed and acuraey of calculation, this three of de C.E.P.A. Battery, Hand dexterity test of E. D.I. T. E. S., Distributed attention and Mechanical Reasoning of D.A.T. Battery; being the best index of validity and reliability in connection with the professional curriculum. This study establishes an initial step in the elaboration of other selective systems of enrrollment based in psychological tests arranged, for the office of Psychometric and Education Psychology of D.O.E. of Educational Minitry of Paraguay.